A distant grave - Taylor, Sarah Stewart (Minotaur Books, 2021)
"In the follow up to the critically acclaimed The Mountains Wild, Detective Maggie D'arcy tackles another intricate case that bridges Long Island and Ireland. Long Island homicide detective Maggie D'arcy and her teenage daughter, Lilly, are still recovering from the events of last fall when a strange new case demands Maggie's attention. The body of an unidentified Irish national turns up in a wealthy Long Island beach community and with little to go on but the scars on his back, Maggie once again teams up with Garda detectives in Ireland to find out who the man was and what he was doing on Long Island. The strands of the mystery take Maggie to a quiet village in rural County Clare that's full of secrets and introduce her to the world of humanitarian aid workers half a world away. And as she gets closer to the truth about the murder, what she learns leads her back to her home turf and into range of a dangerous and determined killer who will do anything to keep the victim's story hidden forever. With the lyrical prose, deeply drawn characters, and atmospheric setting that put The Mountains Wild on multiple best of the year lists, Sarah Stewart Taylor delivers another gripping mystery novel about family, survival, and the meaning of home"--